Analisis Tindak Tutur Perlokusi Pada Iklan Minuman Sprite di Televisi - Putri Fllorenta Fani Diah Aprilia Fitriani Nur; Nur Fitriani (Kantor Bahasa Lampung, 2020)
Advertising is a news that aims to encourage, persuade the general public to be interested in the goods and services offered. Advertising is often offered through various mass media, such as newspapers, magazines, radio and television. The purpose of this study is to describe the form of speech acts of perlocution in sprite beverage advertisements on television and explain the meaning of speech acts of perlocution in sprite beverage advertisements on television. This research is a type of descriptive research with qualitative methods. The data in this study are utterances or sentences that contain speech acts of perlocution in sprite beverage advertisements on television. While the method of data collection using the technique of listening and note taking. The results of this study indicate that the speech acts of perlocution found in sprite beverage advertisements on television are directive, assertive, declarative, commissive and expressive. AbstrakIklan adalah sebuah berita yang bertujuan untuk mendorong, membujuk khalayak ramai agar tertarik pada barang dan jasa yang ditawarkan. Iklan kerap ditawarkan melalui berbagai media massa, misalnya koran, majalah, radio, dan televisi.Tujuan penelitian ini adalah mendeskripsikan bentuk tindak tutur perlokusi pada iklan minuman sprite di televisi dan memaparkan makna tindak tutur perlokusi pada iklan minuman sprite di televisi. Penelitian ini merupakan jenis penelitian deskriptif dengan metode kualitatif. Data dalam penelitian ini adalah tuturan atau kalimat yang mengandung tindak tutur perlokusi pada iklan minuman sprite di televisi. Sedangkan metode pengumpulan data dengan menggunakan teknik simak dan teknik catat. Hasil penelitian ini menunjukkan tindak tutur perlokusi yang ditemukan dalam iklan minuman sprite di televisi, yaitu direktif, asertif, deklaratif, komisif, dan ekspresif.